222. Optimization of pretreatment IMRT dose distribution verification: Bidimensional gaussian kernel implementation. (December 2018) - Errico, F.; Zefiro, D.; Piergentili, M.; Foppiano, F.
Abstract : Purpose: Intensity modulated radiation therapy (IMRT) is a widely used technique delivering a highly conformal dose to the target together with a better sparing of organs at risk with respect to conventional irradiation techniques. Quality assurance (QA) of the generated IMRT treatment plan is of most importance to ensure that the patient receives the planned dose; a two-dimensional array of ionization chambers in a solid phantom can be used for the verification. Different methods exist for comparison of dose distributions and the gamma evaluation is the most commonly used. The aim of this work is to convolve the calculated dose distributions in order to optimize the comparison with the measured data obtained with the MatriXX ionization chamber detector arrays (IBA Dosimetry, Germany). Methods: In this study a bidimensional gaussian kernel, which addresses the ionization chamber volume averaging effect, has been implemented to optimize the comparison of dose distributions for pretreatment patient-specific IMRT QA. It was determined by scanning a single chamber with a slit beam. A point spread function was reconstructed with a Gaussian function obtained with a MATLAB script. The kernel has been tested on head&neck and prostate treatment plans. Results: It has been found that the convolution of the kernel with the treatment planning system calculated dose distribution can improve the comparison respect to the conventional method of IMRT verification. The gamma index passing rate values found with convolution method are higher in all considered clinical cases. Conclusions: The implemented convolution method for the QA of an IMRT treatment plan can improve the comparison between measured and calculated dose distributions.